THE SCHOOL-FAMILY PARTNERSHIP AS A PILLAR OF MEANINGFUL LEARNING: CHALLENGES AND EFFECTIVE PRACTICES - Costa, Karina Ferreira Vicente (Revista Sistemática, 2022)
The partnership between school and family is a fundamental pillar for meaningful learning, grounded in effective communication and shared responsibility. This article investigates the impact of communication and co-responsibility between school and family on the learning process, emphasizing the importance of parental engagement in children's academic, social, and emotional development. Despite challenges such as time constraints and communication barriers, effective practices including bidirectional communication, inclusive family participation, and educational workshops foster stronger school-family bonds. Drawing on academic research and practical experience from lectures and workshops on family bonds and affectivity, this study highlights how collaborative efforts enhance child development and educational outcomes. The findings underscore the essential role of coeducation and affective relationships in sustaining successful school-family partnerships for lifelong meaningful learning.